2000
DOI: 10.1046/j.1365-2702.2000.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with implantable cardioverter‐defibrillators and their conceptions of the life situation: a qualitative analysis

Abstract: Summary· The implantable cardioverter-de®brillator (ICD) is today widely used for the treatment of sudden cardiac near-death episodes as a result of malignant ventricular dysrhythmia.· After examining the literature, only four descriptive studies, all carried out in the USA, with a qualitative analysis based on ICD-patients' own perspectives on their life situation have been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 22 publications
6
50
0
2
Order By: Relevance
“…In a qualitative study 18 of 15 ICD recipients' life situations, the researchers reported the beneficial and intrusive effects of the ICD device and the need for support groups. Use of social supports and support groups improved ability to cope and facilitated psychological adjustment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a qualitative study 18 of 15 ICD recipients' life situations, the researchers reported the beneficial and intrusive effects of the ICD device and the need for support groups. Use of social supports and support groups improved ability to cope and facilitated psychological adjustment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have shown that patients ask for more information about the device and explanations as to why they need an ICD. 4,20 This was also considered important from the healthcare professionals' point of view in the present study. Individual support in combination with a high level of technological knowledge makes it easier for patients to deal with their new life situation.…”
Section: Discussion Of Findingsmentioning
confidence: 88%
“…They tried to be responsive and ask the right probing questions to help the patients with their entire life situation. Today, there is a great deal of knowledge, not only about the technical aspects of the ICD and the patients' physical reactions to it, 14,19,20 but also on how having a device implanted in the body can be experienced as a major life event that may lead to anxiety, depression and impaired quality of life.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Det är emellertid inte alltid möjligt att skapa en sådan tydlig struktur för varje utfallsrum. När fenomenografi används i studier av vidare erfarenhetsfält som hur det är att leva med implanterad defibrillator (126) …”
Section: Fenomenografiunclassified